Pengaruh Struktur Modal dan Ukuran Perusahaan Terhadap Profitabilitas Bank Syariah di Indonesia (Studi Empiris Bank Umum Syariah di Indonesia) - Istiani; Hayati, Sirrul (Jurnal Perbankan Syariah, 2025)
This research is a quantitative associative study aimed at analyzing the influence of capital structure and company size on profitability in Islamic commercial banks in Indonesia. The data used are financial statements from January 2021 to December 2023 obtained from financial statistical reports registered with the Financial Services Authority (OJK). The sampling method used purposive sampling by conducting data tests using IBM SPSS Statistics. Data analysis techniques used classical assumption tests, multiple linear regression tests, and hypothesis tests. Based on the results of the multiple regression test, it was found that simultaneously, capital structure and company size affect profitability, while partially, capital structure does not significantly affect profitability and company size has a positive and significant effect on profitability.